1998
DOI: 10.1161/01.cir.98.16.1597
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Multicenter Comparison of Conventional Anticoagulation Versus Antiplatelet Therapy in Unplanned and Elective Coronary Stenting

Abstract: Background —Dual therapy with ticlopidine and aspirin has been shown to be as effective as or more effective than conventional anticoagulation in patients with an optimal result after implantation of intracoronary metallic stents. However, the safety and efficacy of antiplatelet therapy alone in an unselected population has not been evaluated. Methods —Patients were randomized to conventional anticoagulation or to treatment with antiplatelet therapy alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
217
2
20

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 529 publications
(245 citation statements)
references
References 17 publications
5
217
2
20
Order By: Relevance
“…Prior registries 12,13 and several randomized trials 11,14,15,18 have shown the dramatic reduction in stent thrombosis afforded by the use of aspirin and ticlopidine after successful high-pressure stent implantation. The large sample size of our study allows a reliable estimate of the true stent thrombosis risk and analysis of the factors that may influence this risk.…”
Section: Discussionmentioning
confidence: 99%
“…Prior registries 12,13 and several randomized trials 11,14,15,18 have shown the dramatic reduction in stent thrombosis afforded by the use of aspirin and ticlopidine after successful high-pressure stent implantation. The large sample size of our study allows a reliable estimate of the true stent thrombosis risk and analysis of the factors that may influence this risk.…”
Section: Discussionmentioning
confidence: 99%
“…▶ Figure 3 shows the key results of the ISAR trial. Further important studies like Stent Anticoagulation Restenosis Study (STARS) (26), Full Anticoagulation versus ASpirin and TIClopidine after stent implantation (FANTASTIC) (27) and Multicenter Aspirin and Ticlopidine Trial after Intracoronary Stenting (MAT-TIS) (28) followed and provided important confirmation of the ISAR trial results (25). In concert, these studies paved the way towards a widespread adoption of coronary stenting procedures being accompanied by a DAPT regimen.…”
Section: Introductionmentioning
confidence: 97%
“…Ticlopidine or clopidogrel is structurally related thienopyridine derivates and they exert their antiplatelet effects by inhibiting the adenosine diphosphate dependent pathway of platelet activation (Sharis et al 1998). Trials have shown the superiority of the combination antiplatelet regimen of aspirin and thienopyridines over aspirin alone, or aspirin plus oral anticoagulation with warfarin in preventing stent thrombosis, not only in patients with optimal stent deployment but also in patients who are at high risk of stent thrombosis (Schomig et al 1996;Schuhlen et al 1997;Bertrand et al 1998;Leon et al 1998;Urban et al 1998). Regardless of the stimulus for their activation, the aggregation of platelets that leads to thrombus formation is finally regulated through their membrane binding sites for fibrinogen in the glycoprotein IIb/IIIa receptor complex.…”
Section: Discussionmentioning
confidence: 99%